Numerical methods for singularly perturbed elliptic problems containing two perturbation parameters - O'Riordan, E.; Pickett, M. L.; Shishkin, G. I. (Mathematical Modelling and Analysis, 2006)
A priori parameter explicit bounds on the derivatives of the solution of a two parameter singularly perturbed elliptic problem in two space dimensions are presented. These bounds are used to establish parameter uniform error bounds for a numerical method consisting of upwinding on a tensor product of two piecewise uniform meshes.First Published Online: 14 Oct 2010